A Meta-Analysis Study: The Relationship between Servant Leadership and Organizational Citizenship Behavior - Suyasa, P. Tommy Y. Sumatera; A'yun, Qurrota; Tumanggor, Raja Oloan (Journal of Leadership in Organizations, 2026)
Introduction/Main Objectives: This study examined therelationship between servant leadership and organizational citizenshipbehavior using a meta-analytic approach. The topic is essentialbecause servant leadership emphasizes ethical conduct, empathy, andindividual development contributing to organizationaleffectiveness. Background Problems: Previous studies havereported inconsistent findings regarding the influence of servantleadership on organizational citizenship behavior across various culturaland organizational contexts. This study examined the centralquestion: To what extent is the relationship between servant leadershipand organizational citizenship behavior consistent and significant withinAsian organizational contexts? Novelty: This research synthesized 22quantitative studies conducted across Asia, published from 2015 to2024, making it the first regional meta-analysis to systematicallyexplore the servant leadership and organizational citizenship behaviorrelationship. Prior research has been fragmented and dominated byWestern perspectives, limiting comprehensive insights intocollectivist Asian cultures. Research Methods: A meta-analysis wasconducted using data from 6,023 participants. Statistical procedures,including effect size calculation (r̂), Fisher’s Z transformation,heterogeneity testing, and publication bias assessment, wereconducted using JAMOVI version 2.6.26. Finding/Results: Theresults indicate a significant and positive correlation betweenservant leadership and organizational citizenship behavior (r̂ = 0.359,95% CI [0.274, 0.443]), demonstrating that a higher level of servantleadership is associated with stronger extra-role behaviors amongemployees. No evidence of publication bias was identified.Conclusion: Servant leadership plays a critical role in fostering extrarolebehaviors among employees in Asian organizations. Thesefindings underscore the importance of cultivating servantleadership practices to enhance collaboration, empathy, andsustainable organizational performance.